Biodiesel feasibility study in Surat Thani - Laongtip Wanasuwannakul; Tang, John C.S.; Donyaprueth Krairit; Dimmitt, Nicholas J.; His Majesty King Bhumipol Adulyadej (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Currently, Thailand relies too much on energy import which has negative impact on economic stability and competitiveness. Therefore, they set a goal of consuming 85 million liter per day of BIO in place of petroleum diesel in 2012. Regarding government policy, researcher has studied on biodiesel feasibility in different plant sizes; 100 and 200 TPD, and found that the critical factors of project feasibility are CPO price, biodiesel price, glycerin price, and government support. Under typical conditions, 200 TPD biodiesel project is a suitable plant size for investment because of benefits from economies of scale. Moreover, in conjunction with the CDM project is another option to increase the return of biodiesel project because it can gain benefits from reduction of greenhouse gases with Certified Emission Reductions (CERs). Referring to benefit at macro level, the government needs to encourage people to substitute blended biodiesel for HSD even without significant price advantage. Additionally, in the initial phase of biodiesel usage campaign, the government should exempt all kinds of taxes on biodiesel (B 100) and offer the subsidy to investors. Lastly, the government should increase the number of oil stations providing blended biodiesel throughout the country.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2007
Keywords: Biodiesel fuels -- Thailand -- Surat Thani